KARAKTER PENYIAR KREATIF DALAM SIARAN BERITA DI RADIO SEILA 104.3FM BATAM - Angga Aminudin; Nani Nurani Muksin (AT-TAWASUL, 2022)
As a media provider of information, each radio has its own concept in carrying out its broadcast format. As in Indonesia, there are many radios with various broadcast formats with multi-segment listeners. Radio Seila FM Batam has a general broadcast format, in the sense of combining entertainment, news and music in one broadcast format with Islamic religious nuances. It turns out that in a few years, the program that is most in demand by listeners is the program "Topik Berita Pagi". The announcer of the program "Topik Berita Pagi" has a significant role in the process of developing and delivering information to listeners. The character that is built and prepared by the announcer in order to attract listeners is done professionally and creatively. This study aims to determine the creativity of the announcer of the program "Topik Berita Pagi". The qualitative method used is descriptive phenomenology based on Husserl's philosophy. This descriptive phenomenology is used to develop the structure of the broadcaster's life experience in collaboration with the news program team who is responsible for preparing all news broadcast content with a duration of about 90 minutes. It can be seen that the most prominent creative announcer characters from this program are; Have adequate vocal quality, reliable in adlibbing and script reading, up-to-date and broad in knowledge, deep understanding of radio segments, showing sympathy and empathy for listeners, able to generate fresh and solution ideas, Able to work in a team and "Be Your Self". At a radio station, a creative announcer who brings an event certainly has strategic value. Because the latest news is packaged in such a way, delivered to the listeners very well and interestingly, causing a positive response from the listeners. This will be useful in radio's efforts to maintain its existence in the broadcasting world